Internalisasi Karkter Melalui Living Qur’an Pada Madrasah Ibtidaiyah - Parapat, Fadilani Azmi; Lubis, Cici Novianti (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to understand the implementation of character internalization through the Living Qur'an at Al-Washliyah Labuhanbatu Utara Elementary School. This qualitative study employs a phenomenological approach to explore the experiences of students and educators in applying Qur'anic values in daily life. The findings reveal that the Living Qur'an is implemented through Qur'anic education that goes beyond mere memorization, emphasizing understanding and practicing moral values such as honesty, perseverance, and mutual assistance. The internalization strategies employed include teacher modeling, group discussions, and experiential learning approaches. However, this study also identified several challenges, such as limited facilities, a lack of deep understanding of the Living Qur'an among educators, and inconsistencies between the national curriculum and religion-based character development. Despite these challenges, the implementation of the Living Qur'an at Madrasah Ibtidaiyah Al-Washliyah has had a positive impact on the character development of students. This study is expected to contribute to the development of a Qur'an-based character education model in madrasahs.